Pengaruh Faktor Sosial dan Faktor Pribadi Terhadap Sikap dan Minat Pembelian Film Bajakan (Studi pada Masyarakat Kota Malang) - Utama, Satria Putra; Rochman, Fatchur (Jurnal Aplikasi Manajemen, 2013)
The purpose of this research is to identify and quantify the influence of social factors towards pirated movies buying interest on the citizen of Malang, the influence of personal factors towrds pirated movies buying interest on the citizen of Malang, Influence attitudes towards pirated movies buying interest on the citizen of Malang, the influence of social factors towards pirated movies buying interest that is mediated by attitudes in the citizen of Malang, the influence of personal factors towards pirated movies buying interest that is mediated by attitudes in the citizen of Malang. Type of this research is a survey research, which takes samples from a population and use the questionnaire as an instrument of primary data collection. Thus, this research was categorized as an explanatory research. The number of respondents in this study as many as 100 people. Method of data collection methods questionnaire is done, then the data processed through SPSS software, tool of analysis in this study using path analysis. Results showed that (1) social Factors encourage interest in the purchase of pirated films, (2) personal Factors encourage interest in the purchase of pirated movies, (3) attitude encourage interest in the purchase of pirated movies, (4) social Factors are mediated by the attitude of encourage interest in the purchase of pirated movies, (5) the personal Factors are mediated by the attitude encourage interest in the purchase of pirated movies.